Pengaruh Biaya Produksi Dan Biaya Operasional Terhadap Laba Perusahaan Farmasi Di Indonesia Pada Kurun Waktu 2016 - 2018 - Budiono, Anshori; Nofriandi, Nofriandi; Herawati, Tuti; Zaharuddin, Zaharuddin; Supriyadi, Supriyadi (Jurnal Etnik: Ekonomi-Teknik, 2021)
Consumer goods have direct demand characteristics, meaning that consumers are the determinants of purchasing consumer goods. On the other hand, the pricing of consumer goods is determined by retailers, not by producers. Under these conditions, the production and operational costs for producing goods must be as small as possible so that the retailer's selling price to the public can be accepted by consumers.The purpose of this study is to see the effect of increasing production costs and operating costs of pharmaceutical companies in Indonesia in the period 2016 to 2018. The research method is carried out by processing quarterly data on production costs, operating costs, and net income of two pharmaceutical companies in Indonesia during that period. The linearity test of the relationship was carried out by Spearman, Kendall, and Pearson correlation analysis. Meanwhile, to get the relationship, multiple regression was carried out using the Ordinary Least Square and Weighted Least Square methods From the data analysis, using the OLS method, the coefficient values ??of the increase in production costs and operating costs are 0.393 and 0.002. Meanwhile, the WLS method obtained the coefficient values ??of 0.382 and 0.010. This study concludes that there is a potential for increasing profits which is dominated by production factors. In this case, there is the potential to increase the company's profit by increasing production capacity.